Supporting Environmental Sustainability: An Evaluation of World Bank Group Experience, 1990-2007 - World Bank (Washington, DC, 2012)
The Bank Group's lending and non-lending support for environmental sustainability has increased and improved over the past 15 years. But the institution needs to raise the priority it accords to this area of rising concern, strengthen internal cooperation, and work more effectively with its government and private partners to help countries to get better results in addressing environmental challenges. The Bank, International Finance Corporation (IFC), and Multilateral Investment Guarantee Agency (MIGA) should jointly develop and commit to a new environmental strategy and ensure that environmental priorities enter fully into their strategic directions as well as in regional and country assistance programs, focusing in particular on underperforming regions and sectors and countries with the most significant environmental problems. The Bank Group should step up its support for public-private partnerships and take greater advantage of the private sector's potential for technology development and transfer, transformation toward clean and low-carbon technologies, and sustainable supply chains, while continuing to help countries strengthen environmental governance.